Evidence-Based Teaching: Applying Cognitive Science in Educational Practice - Faruq Al-Kholidy; Zuyyina Harby (Innovative Journal of Educational Research and Insights, 2026)
This study examines the application of cognitive science principles in educational practice through the framework of evidence-based teaching. The study employed a qualitative library research design using a descriptive-analytical approach. Data were collected from books, peer-reviewed journal articles, conference proceedings, and scholarly publications related to cognitive science, learning sciences, and educational psychology. The collected data were analyzed using thematic content analysis to identify major themes associated with effective instructional practices. The findings reveal that cognitive principles, including cognitive load management, retrieval practice, metacognition, self-regulated learning, and effective feedback, significantly contribute to improving student motivation, engagement, and academic achievement. Furthermore, appropriate instructional design, collaborative learning, and technology integration support meaningful learning experiences and enhance educational effectiveness. The study concludes that evidence-based teaching provides a practical framework for translating cognitive science research into classroom practice. The findings offer important implications for educators, policymakers, and teacher education programs in promoting effective, learner-centered, and scientifically informed instructional practices.